ANALYSIS OF INTEGRATION OF CASSAVA AGRIBUSINESS SUBSYSTEM AT PANCUR BATU SUB-DISTRICT DELI SERDANG REGENCY - Hotden L. Nainggolan; Johdikson Aritonang (AGRIUM: Jurnal Ilmu Pertanian, 2017)
This research aims to; a) knowing the constraints of cassava agribusiness development in the District Pancur Batu, b) determine the condition of the relationship between sub-systems that play a role in agribusiness of cassava in District Pancur Batu, c) determine the condition of the marketing of cassava in  District Pancur Batu. This research was conducted in the District of Pancur Batu, with descriptive analysis method. Based on the research concluded; a) The condition of farm production of cassava in District Pancur Batu categorized quite good, but not yet showing the development of production. Cassava been farming community as an activity for easy maintenance process and does not require intensive care, b) the marketing conditions cassava is still modest and relatively fixed. Market chains are short so that share margin the biggest can be obtained by the manufacturer, c) Relationship between the subsystems of agribusiness cassava distinguished relationship is not tight and continuous on subsystem providers the means of production by farmers and relationships that continuously into sub systems production, marketing and processing because there is a relationship mutually beneficial. Based on the results suggested; a) government Deli Serdang undertake training and extension to farmers to increase farm production of cassava, b) the government of Deli Serdang provide incentives to farmers to stimulate an increase in farm production of cassava in District Pancur Batu, c) the government of Deli Serdang attention to marketing conditions cassava, by providing information and of action clear to the farmers market in the district of  Pancur Batu. Keywords: agriculture, agro-industry, cassava